Dilemas em Aconselhamento de Carreira - Cardoso, Paulo (2008)
This paper aims to reflect and discuss some of the dilemmas met during career counselling. Based on the idea of dilemma as a transtheoretical concept, I start by defining this concept within psychological aid in general, moving then to specify it in the context of career counselling. Some dilemmas are presented, in their ethical and technical dimensions as well as possible solutions. This paper highlights the advantages of the constructivist perspective in career counselling to deal with the dilemmas experienced by the counsellor. It is also stressed the importance of accepting the dilemmatic experience in prompting a critical attitude towards the process of career counselling.